Retrospect: The Scott Polar Research Institute, 1920–45 - F. D. (Polar Record, 1945)
It is rarely possible to state exactly when a new idea is born, for such things are apt to take shape gradually, attaining full stature by slow degrees. Yet the germ of a polar institute certainly emerged during November of 1912 on the slopes of Mount Erebus when Raymond E. Priestley and I were making a geological survey of the district round Shackleton's old hut at Cape Royds. We were but amplifying a survey done three years earlier by Professor David, Mawson and Priestley himself, and the question arose as to where their original notes and figures would be when we returned. Naturally that led to a debate upon the need for a central repository for field records. About the same time I had discussions with Charles Wright, our ice-physicist, on the best way of passing on to future explorers the small improvements in sledging gear and camp equipment which we had devised and tested, discussions which veered in the same direction.